Rio de Janeiro residents’ perceptions of the 2016 Olympics in the pre-games period - Zouain, Deborah Moraes (2019)
Between 2014 and 2016, Rio de Janeiro hosted two mega sport events – the Fédération Internationale de Football Association World Cup and the Olympic Games – which generated changes in the city. This study sought to analyse Rio residents’ perceptions in the lead-up to the latter games. A quantitative survey was conducted face-to-face with a sample of 404 residents, exactly one year before the Olympics. The data indicated that the residents found the pre-game period troubling because of uncertainties regarding the city’s desired Olympic legacy. Residents’ routines were impacted by either traffic issues or media reports that generated expectations and apprehension. The pre-Olympic period was marked by protests, concerns about overspending, construction delays and fears about the mega-events’ success. However, residents’ perceptions included clear expectations regarding the event legacy’s implications for tourism businesses and the destination’s visibility, as well as lasting improvements affecting tourism and sport activities.